Protective effect of hormone therapy among women with hysterectomy/oophorectomy. Issue 4 (9th February 2017) - Chen, L.; Mishra, G.D.; Dobson, A.J.; Wilson, L.F.; Jones, M.A.
Abstract: STUDY QUESTION: Does exposure to menopausal hormone therapy (MHT) in mid-aged women alter their risk of cardiovascular disease (CVD) mortality and all-cause mortality? SUMMARY ANSWER: MHT soon after menopause is unlikely to increase the risk of CVD mortality or all-cause mortality and may have a protective effect for women with hysterectomy/oophorectomy. WHAT IS KNOWN ALREADY: The balance of benefits and risks of MHT are currently unclear and may differ according to when treatment starts and whether women have an intact uterus. STUDY DESIGN, SIZE, DURATION: A total of 13 715 participants from the mid-aged population-based cohort (born 1946–1951) of the Australian Longitudinal Study on Women's Health (ALSWH) were followed from 1998 to 2013. PARTICIPANTS/MATERIALS, SETTING, METHODS: The measures included cardiovascular and all-cause mortality, exposure to MHT and menopausal status (based on 3-yearly self-reports). Electronic prescriptions data on MHT were also available from mid-2002 onwards. At each follow-up survey wave, participants were classified as: an existing user of MHT, an initiator of MHT or a non-initiator of MHT. MAIN RESULTS AND THE ROLE OF CHANCE: After adjusting for confounding variables, existing users of MHT had a reduced risk (hazard ratio 0.63; 95% CI, 0.43–0.92) of CVD mortality compared with non-initiators. Insufficient evidence of an association was identified for initiators of MHT (0.66; 0.35–1.24). For all-cause mortality, risks were reduced for both initiators (0.69; 0.55–0.87) and existing users (0.80; 0.70–0.91). In a subgroup analysis, women with hysterectomy/oophorectomy had lower risks of CVD mortality for both initiators (0.14; 0.02–0.98) and existing users (0.55; 0.34–0.90), but no evidence of an association was found for women whose MHT commenced during or after menopause. Similarly for all-cause mortality, only the women with hysterectomy/oophorectomy had lower risks for both initiators (0.47; 0.31–0.70) and existing users (0.69; 0.58–0.82). LIMITATIONS, REASONS FOR CAUTION: Limitations include the observational nature of the study, the small number of deaths, MHT use being self-reported and the classification of menopausal status also being based on self-reported information. WIDER IMPLICATIONS OF THE FINDINGS: Women considering MHT soon after menopause can be reassured that the treatment is unlikely to increase their risk of CVD mortality or all-cause mortality. STUDY FUNDING/COMPETING INTEREST(S): The Australian Longitudinal Study on Women's Health is funded by the Australian Department of Health. G.D.M. is funded by the Australian Research Council Future Fellowship. L.C. was funded by a China scholarship council (CSC) graduate scholarship. All authors report no conflict of interest. TRIAL REGISTRATION NUMBER: N/A